Ethno-cultural tourism as a promising area for inter-municipal and inter-regional cooperation in the development of rural areas in the Republic of Bashkortostan and the Chelyabinsk region - V. Ya. Akhmetov (Вестник университета)
In the context of the coronavirus pandemic and the introduction of certain restrictions on movement between some countries, there is an increase in demand for domestic tourism in the constituent entities of the Russian Federation, including in the Republic of Bashkortostan. One of the promising, but still underdeveloped types of domestic tourism in Bashkortostan and the neighboring Chelyabinsk region is ethnocultural tourism, the potential of which is huge in terms of opening new jobs, organising new small and medium-sized enterprises. It can be considered as a promising direction for the diversification of the rural economy and tourism business, which can dramatically increase the income of the villagers and, in general, the quality of life in rural areas. In addition, it contributes to the preservation of tangible and intangible objects of historical memory, in particular, folk crafts and crafts, customs and traditions, and skills in the production of unique national cuisine products. On the example of depressed rural areas of the Republic of Bashkortostan and the Chelyabinsk region, the author updates the feasibility of enhancing the areas of intermunicipal and interregional cooperation in the field of rural ethnocultural tourism, including through the introduction of additions and changes to federal, regional and municipal programmes for the socio-economic development of the village, small and medium-sized businesses, agricultural cooperation, tourism and the inclusion in them of proposals to support ethnic entrepreneurship and the formation of ethnotourist clusters. The organisation of national (ethno) villages in the Argayashskiy, Kunashakskiy districts of the Chelyabinsk region and in the south-north-eastern regions of Bashkortostan, inter-municipal and inter-regional ethno-tourist clusters can contribute to a more efficient use of the ethno-cultural potential of the indigenous Bashkir population living in them, the preservation of their culture, traditions and customs, activating ethno-tourism and improving the quality of life of the villagers.